Karakteristik Bubuk Alginat dari Alga Coklat Sargassum sp. pada Perlakuan Waktu dan Suhu Maserasi - Danu Subagan, Kadek Ngurah Ghandhi; Suhendra, Lutfi; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 1 (2020): MaretDO - 10.24843/JRMA.2020.v08.i01.p11, 2020)
Sargassum sp. is an example of a brown algae plant that produces alginates in the form of an organic polysaccharide polymer composed of two units of L-guluronic acid and D-mannuronic acid monomers. The polymer is hydrophilic, that is, alginate is a linear molecule with a high molecular weight, so it is easy to absorb water causing alginate compounds can be used as emulsifiers. This research aims to know the effect of maceration time and temperature on the characteristics of alginate powder from brown algae Sargassum sp. and determine the best maceration time and temperature to produce alginate powder from brown algae Sargassum sp. This research used a Factorial Randomized Block Design. The first factor is time (A) which consists of 3 levels, namely 1 hour, 2 hours and 3 hours. The second factor is temperature (B) which consists of 3 levels namely 50°C,60°C,70°C. Each treatment were grouped into 2 based on the time of implementation so that 18 units of the experiment were obtained. The variables observed were the yield, water content, ash content, and viscosity. The data obtained were then analyzed by variance analysis and continued using the HRD method (Honest Real Difference). The results showed that the treatment of maceration time and temperature had a very significant effect on the observed variables namely yield, moisture content, ash content, and viscosity. The results showed that the treatment of 3 hours with a temperature of 70±1°C was the best treatment to produce alginate powder from brown algae Sargassum sp. with yield characteristics 39.44±0.06 %, water content 9.86±0.04 %, ash content 31.75±0.02 %, and viscosity value 19.00±1.41 cPs. Keywords: maseration, time, temperature, alginate, Sargassum sp.